A 'class of no political weight'? Interracial Marriage, Mixed Race Children and Land Rights in Southern New Zealand, 1840s-1880s. Issue 3 (3rd July 2019) - Wanhalla, Angela; Stevens, Kate
ABSTRACT: Interracial marriage was a defining feature of interaction between local Ngāi Tahu and newcomers in southern New Zealand from the early nineteenth century. Scholarship has explored the importance of such relationships to development of New Zealand's early resource-based economies and to colonial assimilation policies. However, the experiences of cross-cultural households and families in colonial New Zealand are less well documented. Using a body of writing produced by fathers and their mixed-race children in response to land claims investigations in the mid-nineteenth century, this article explores the political, economic and social world of interracial families in southern New Zealand. The correspondence over land rights reveals the ongoing importance of kinship ties through generations as colonial expansion impinged on these communities. Through petitioning and letter writing, fathers and children contested what marriage and family meant and strategically asserted their individual and collective identity in the face of increasing land dispossession and economic hardship.